COMPETITION BETWEEN IRON- AND CARBON-BASED COLLOIDAL CARRIERS FOR TRACE METALS IN A FRESHWATER ASSESSED USING FLOW FIELD-FLOW FRACTIONATION COUPLED TO ICPMS - Lyvén B.; Haraldsson C.; Hassellöv M.; Turner D.R.; Andersson K. (My University, 2003)
Flow field–flow fractionation (FlFFF) coupled to an inductively coupled plasma mass spectrometer (ICPMS) has been used to determine the chemical composition of colloids from a freshwater sample as a function of size. Organic carbon and iron are the most abundant colloidal components, and are considered as the major carrier phases for other chemical elements present. The size distribution of organic carbon colloids shows a single peak with an estimated hydrodynamic diameter between 1 and 1.5 nm, while the iron colloids show a more complex distribution centred at larger colloid sizes with estimated hydrodynamic diameters up to 5 nm. The association of 32 trace elements with these two carrier colloids has been quantified by deconvolution analysis, and the resulting distributions are shown to be chemically consistent. The observed distributions are also shown to be broadly consistent with predictions from speciation modelling for the subset of 8 elements for which appropriate stability constants are available.